The Role of Empowerment of Dumai Science Teachers Association (MGMP IPA) in improving the Professional Competency of Junior High School Science Teacher - Yulvisriani, Yulvisriani; Suryawati, Evi; Suzanti, Fitra (FKIP-Universitas Riau, 2020)
This study aims to look at the role of empowerment Science Teachers Association (MGMP IPA) in improving the Professional competence of science teachers in the city of Dumai, Indonsia. This type of research was descriptive qualitative. The population of this study were all teachers in MGMP IPA Dumai. The research sample was 70 teachers who were members of the MGMP IPA Dumai. Data collection technique were using questionaires and test. The result showed that average professional ability of the teachers was 74 in good categories, pedagogical average was 61 in the moderate category and PCK was 56 in the moderate category. This shows that MGMP IPA Dumai has not fully played a role in increasing the professional competence of teachrers.